Mathematics Learning Experiences and Problem-Solving Engagement Among Junior High School Learners in a Rural Philippine Secondary School Context: Insights from Abuyo National High School - ABELLARA, JOYCE (Studies in Technology and Education, 2026)
Mathematics learning experiences and problem-solving engagement significantly influence learners’ conceptual understanding, critical thinking, participation, and academic confidence in secondary education. This study explored the mathematics learning experiences and problem-solving engagement among Junior High School learners at Abuyo National High School, a rural secondary school in Nueva Vizcaya, Philippines. Anchored on Constructivist Learning Theory and Experiential Learning Theory, the study employed a descriptive qualitative research design to examine learners’ classroom experiences, participation, instructional interactions, and engagement in mathematical problem-solving activities. Participants included selected Junior High School learners and mathematics teachers of Abuyo National High School. Data were gathered through semi-structured interviews, focus group discussions, classroom observations, and document analysis. Braun and Clarke’s (2006) thematic analysis approach was utilized in analyzing the gathered data. Findings revealed that collaborative learning activities, contextualized mathematics instruction, supportive teacher facilitation, and interactive problem-solving tasks significantly contribute to learners’ engagement and conceptual understanding in mathematics. Learners demonstrated greater participation and confidence when mathematics lessons were connected to real-life experiences and practical applications. The findings further revealed that positive teacher-learner relationships and learner-centered instructional approaches strengthen learners’ motivation and willingness to participate in mathematical discussions and problem-solving activities. However, challenges such as mathematics anxiety, limited conceptual understanding, fear of making mistakes, insufficient instructional resources, and varying learner abilities negatively affected participation and engagement. The study concludes that meaningful mathematics learning experiences and supportive instructional environments significantly contribute to learners’ problem-solving engagement and mathematical understanding in rural secondary school contexts. Strengthening contextualized instruction, collaborative problem-solving activities, and learner-centered pedagogical approaches is recommended to improve mathematics engagement and learning experiences among Junior High School learners. Keywords: mathematics learning, problem-solving engagement, learner experiences, mathematics education, qualitative research, rural education, secondary education